1983
DOI: 10.1002/ar.1092050404
|View full text |Cite
|
Sign up to set email alerts
|

The blood–testis barrier in the toad (Bufo arenarum hensel): A freeze‐fracture and lanthanum tracer study

Abstract: Intercellular junctions between Sertoli cells in the toad testis were studied by freeze-fracture and electron-opaque intercellular markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
11
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
6
11
0
1
Order By: Relevance
“…According to LOFTS (1974), the primary spermatogonia are the largest germ lineage cells and rest on the basal lamina adjacencies of the seminiferous elements, associated with follicular cells. Similar observations were documented in Scinax fuscovarius and in another species: Bufo arenarum (CAVICCHIA and MOVIGLIA 1983); Caudiverbera caudiverbera (HERMOSILLA et al 1983); Pachymedusa dacnicolor (RASTOGI et al 1988); Hyla ranki (TABOGA and DOLDER 1991) and Odontophrynus cultripes (BÁO et al 1991). In Hyla ranki, the volume of the primary spermatogonia can reach the triple of the other cells in differentiation and its big nucleus, very irregular and multilobed, results in a reduction of the cytoplasmatic area (TABOGA 1990).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…According to LOFTS (1974), the primary spermatogonia are the largest germ lineage cells and rest on the basal lamina adjacencies of the seminiferous elements, associated with follicular cells. Similar observations were documented in Scinax fuscovarius and in another species: Bufo arenarum (CAVICCHIA and MOVIGLIA 1983); Caudiverbera caudiverbera (HERMOSILLA et al 1983); Pachymedusa dacnicolor (RASTOGI et al 1988); Hyla ranki (TABOGA and DOLDER 1991) and Odontophrynus cultripes (BÁO et al 1991). In Hyla ranki, the volume of the primary spermatogonia can reach the triple of the other cells in differentiation and its big nucleus, very irregular and multilobed, results in a reduction of the cytoplasmatic area (TABOGA 1990).…”
Section: Discussionsupporting
confidence: 68%
“…This organization in buncdles is related in several species and it is observed that the cells keep a fundamental morphofunctional relationship with the germ lineage cells, which is still more evident during the spermiogenic process (CAVICCHIA and MOVIGLIA 1983;RASTOGI et al 1988;TABOGA 1990;BÁO et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The basal membrane resulted in the development of a permanent separation between germinal and interstitial testicular compartments in fishes, amphibians, and all amniotes (Grier, 1992). The same type of spermatogenesis was confirmed in D. minutus (Santos and Oliveira, 2007) and occurs in all anuran species described to date, thus corroborating a fundamental characteristic of spermatogenesis within these follicular structures, where all cells of a group are always in the same differentiation stage (Lofts, 1974;Cavicchia and Moviglia, 1983;Rastogi et al, 1988;Bá o et al, 1991). These traits also occur in fishes (Grier et al, 1981;Cruz-Landim et al, 2003).…”
Section: Discussionsupporting
confidence: 59%
“…The general characteristic of a cyst is the formation of an hematotesticular barrier between these cells. It has been suggested that this mechanism maintains the compositional differences between blood or hemolymph and the testicular fluid, resulting in the formation of a microenvironment that is appropriate for the development of haploid germ cells (Cavicchia and Moviglia, 1983;Bergmann et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Aspectos morfológicos e funcionais da espermiogênese têm sido descritos em vários estudos com anuros, especialmente no que concerne aos complexos eventos envolvendo formação do acrossomo (SPRANDO & RUSSELL, 1988;RASTOGI et al, 1988), compactação cromatínica, alongamento nuclear (REED & STANLEY, 1972;CAVICCHIA & MOVIGLIA, 1983;BÁO et al, 1991;LEE & JAMIESON, 1992LEE & KWON, 1992;TABOGA & DOLDER, 1998) e formação do flagelo (TABOGA & DOLDER, 1993).…”
unclassified